Cultural intelligence model based on value “pintar tuntang harati” for growing peace in senior high school students in Palangka Raya City - Fendahapsari Singgih Sendayu; Sunaryo Alidha Sunaryo (AL-ASASIYYA: Journal Of Basic Education, 2020)
Cultural intelligence is built on the ability of self to cultivate awareness in accommodating cultural experiences encountered in everyday life as a counterweight of cognitive intelligence that can be applied in certain attitudes in everyday life. Cultural intelligence occurs when there is interaction among a group of individuals, both social interaction and cultural interaction. Implementation of local cultural values in the development of the educational process becomes very important in an effort to strengthen the character of the nation. The value of the culture of local wisdom about "Pintar Tuntang Harati" which contains meaning related to attitude, the person said to be a person who has good attitude, praised, intelligent, tenacious, tough, able to control his emotions, know when to talk and when silent, responsible, respectful, skilled at putting himself environmentally, humbly and peace loving. The value of culture " Pintar Tuntang Harati " is the value of cultural intelligence of ancestral heritage that is important to be empowered in fostering peace education that is able to form the character of student peace in the form of attitude and behavior that shows love,affection, mutual respect,appreciate, and friendship on himself  or to someone else different from him.